Evolution of the structural orientation in polyacrylonitrile precursors during stabilization revealed by in-situ synchrotron wide-angle X-ray diffraction and polarized infrared spectroscopy. (December 2017) - Zhou, Yiran; Han, Xu; Hu, Xiaoyuan; Xu, Lianghua; Cao, Weiyu
Evolution of the orientation structures of polyacrylonitrile (PAN) precursors during thermal stabilization was investigated on the basis of in situ temperature-dependent measurements including synchrotron wide-angle X-ray diffraction and polarized infrared spectroscopy. The results indicated that the Hermans orientation factor of PAN crystallites increased firstly and then decreased in the process of stabilization, while the orientation of molecular chains showed a two-stage decrease. These were mainly attributed to the thermal relaxation of molecular chains and the cyclization reactions, which also resulted in the physical shrinkage as well as the chemical shrinkage apparently observed from the thermal mechanical curves of the precursor.